IMPACT OF SPORTS FACILITIES ON AGGRESSION AND ANXIETY AMONG PLAYERS AT GULBARGA UNIVERSITY - Havappgol, Jayalaxmi S; Malipatil, Rajkumar P (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study explores the relationship between sports facilities and psychological factors such as aggression and anxiety among players at Gulbarga University. The availability, quality, and accessibility of sports infrastructure can significantly impact athletes’ mental well-being, performance, and behavior. The research employs a mixed-method approach, incorporating surveys and interviews with university athletes to assess their perception of sports facilities and their psychological state. Data were analyzed using statistical methods to determine correlations between the quality of sports infrastructure and levels of aggression and anxiety. The findings suggest that well-equipped and maintained sports facilities contribute to lower anxiety levels and reduced aggression by promoting a sense of security, confidence, and better stress management among players. Conversely, inadequate or poorly maintained facilities may lead to frustration, increased anxiety, and heightened aggression. These results underline the necessity for universities to invest in quality sports infrastructure to enhance both physical and psychological well-being. The study concludes with recommendations for improving sports facilities to create a more positive and psychologically beneficial environment for university athletes.